Membina 'Qolbun Salim': Integrasi Prinsip Pengasuhan Islami dengan Praktik Psikologi Modern pada Anak Usia Dini - Suminah; Mujiburrahman; Salami Mahmud; Safrilsyah (Jumper: Journal of Educational Multidisciplinary Research, 2026)
This study aims to develop the Integrative Qolbun Salim Model (MIQS) as a conceptual framework integrating Islamic parenting principles with modern developmental psychology in early childhood education. A qualitative approach was employed through a Systematic Literature Review (SLR) combined with Conceptual Model Development. Literature was retrieved from Scopus, Web of Science, Dimensions, ERIC, and Google Scholar following the PRISMA 2020 guidelines. Data were analyzed using open coding, axial coding, thematic synthesis, and conceptual integration. The synthesis of thirty core manuscripts generated six major themes: Islamic spiritual foundation, parent–child emotional attachment, emotion regulation and mental health, positive parenting based on modern psychology, Islamic role modeling in family education, and the integration of Islamic parenting with contemporary developmental psychology. These findings resulted in the MIQS framework consisting of input, process, and output components, positioning Qolbun Salim as the core construct of holistic child development. The model offers both a theoretical contribution and a practical framework for families and early childhood education institutions in fostering children's spiritual, emotional, social, and psychological well-being.